1992
DOI: 10.1002/1097-0142(19920101)69:1<187::aid-cncr2820690131>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

DNA level and stereologic estimates of nuclear volume in squamous cell carcinomas of the uterine cervix. A comparative study with analysis of prognostic impact

Abstract: Grading of malignancy in squamous cell carcinomas of the uterine cervix is based on qualitative, morphologic examination and suffers from poor reproducibility. Using modern stereology, unbiased estimates of the three‐dimensional, volume‐weighted mean nuclear volume (nuclear v̄Mv), were obtained in pretreatment biopsies from 51 patients treated for cervical cancer in clinical Stages I through III (mean age of 56 years, follow‐up period >5 years). In addition, conventional, two‐dimensional morphometric estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Altered nuclear scaling is associated with many cancers, and cytopathologists monitor graded increases in nuclear size for cancer diagnosis and prognosis (Zink et al, 2004;Chow et al, 2012;. Importantly, nuclear size increases in cancer are frequently independent of gross ploidy changes (Lindberg, 1992;Miyamoto et al, 1992;Sørensen et al, 1992;Wang et al, 1992;Dangou et al, 1993;van Velthoven et al, 1995;Sørensen, 1996;Dey, 2010), implicating potential cytoplasmic contributions to altered nuclear size (Goehring and Hyman, 2012). It is unknown whether changes in nuclear size contribute to carcinogenesis, and answering this question necessitates an understanding of the mechanisms responsible for regulating nuclear size.…”
Section: Introductionmentioning
confidence: 99%
“…Altered nuclear scaling is associated with many cancers, and cytopathologists monitor graded increases in nuclear size for cancer diagnosis and prognosis (Zink et al, 2004;Chow et al, 2012;. Importantly, nuclear size increases in cancer are frequently independent of gross ploidy changes (Lindberg, 1992;Miyamoto et al, 1992;Sørensen et al, 1992;Wang et al, 1992;Dangou et al, 1993;van Velthoven et al, 1995;Sørensen, 1996;Dey, 2010), implicating potential cytoplasmic contributions to altered nuclear size (Goehring and Hyman, 2012). It is unknown whether changes in nuclear size contribute to carcinogenesis, and answering this question necessitates an understanding of the mechanisms responsible for regulating nuclear size.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,6,8,10,14 The strength of our prospective study is that this is the first that presents 10-year results of flow cytometric DNA analysis from fresh tumor samples. In fact, it is known that histograms from paraffin-embedded material are less accurate than those from fresh tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that tumor ploidy, DNA index, and SPF, obtained by flow cytometry, are strong and independent prognostic parameters in comparison with standard pathologic factors. 3,4,6,8,10,14 Other studies did not confirm these results. 2,5,7,9,11Y13,15,16 These conflicting evidences hampered a wider diffusion of DNA ploidy determination as standard practice in cervical carcinoma.…”
mentioning
confidence: 94%
“…An unbiased stereologic method has been developed for estimating the volume‐weighted MNV from histologic sections ( 11 ) . A significant correlation between the MNV and the survival has been demonstrated in patients with bladder carcinomas ( 14 ) , malignant melanomas ( 15 ) , squamous cell carcinomas of the uterine cervix ( 16 ) , breast cancer ( 17 ) and squamous cell carcinoma of the lung ( 18 ) . However, no correlation has been observed between the MNV and the survival of patients with epithelial ovarian cancer ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%